Learning statistics using infographics: A powerful tool to engage communication students in learning activities - Silvestre, Cláudia (2021)
We live in an information-driven society, where statistics play an important role, and are used in many different fields, for instance, business, political, advertising or social activities. Furthermore, statistics have been used to help decision makers develop informed policies that impact millions of people. Consequently, they constantly appear in news on social media, which leads us to a great challenge – promoting statistical literacy. Communication students are not only consumers, they will also be producers of statistical news. So, they need to be able to search, read, critique and communicate statistical information accurately. That is a big challenge for us, as teachers, since our communication students do not have a great interest in these subjects. In addition to this, some of them do not feel at ease with numbers. We have been developing a project in order to keep our students engaged in class activities and motivate them to learn statistics based on social media news, mostly about COVID-19 pandemic. This project has been carried out in three phases. In the first one, in order to develop critical sense and become aware of possibility about biased or incorrect information, students analyze statistical information available on social media, including data sources and their validity. Infographics as a form of reporting statistical data is the second phase, in which students explore other ways of visualizing and communicating data. Occasionally they may improve the way statistical information is communicated. After these two phases students should be able to make and discuss their own infographics avoiding most common errors. The advantages/benefits of this project can be summarized as follows: (1) Identification of the best data source according to their goal; (2) Choice of statistical methods to report data properly; (3) Communication of data in an accurate way and candy eye manner; (4) Promotion of class debate; (5) Development of critical thinking.